Exploration of TCM Syndrome Differentiation and Treatment of Chest Bi with Yin Deficiency and Blood Stasis - Yuan, Yunjiao; Chen, Jinfeng (Journal of Contemporary Medical Practice, 2025)
In traditional Chinese medicine, thoracic obstruction, as an independent disease category, has long been widely studied and applied. According to the theory of traditional Chinese medicine, chest obstruction is caused by qi stagnation, yin deficiency and blood stasis, which leads to poor qi and blood circulation in the chest. Chest obstruction, as one of the important diseases in the field of traditional Chinese medicine, has important theoretical and clinical value. Traditional Chinese medicine has accumulated rich experience in the understanding and treatment of chest obstruction, and achieved certain clinical results by regulating yin deficiency, promoting blood circulation and removing blood stasis. However, the theoretical exploration of chest obstruction due to yin deficiency and blood stasis is still relatively insufficient, and it is necessary to further study its pathogenesis and TCM treatment methods in order to improve the understanding and treatment effect of chest obstruction. The purpose of this paper is to explore the theory of yin deficiency and blood stasis in chest obstruction, and through literature review, to deeply analyze the mechanism of yin deficiency and blood stasis in chest obstruction and the principles and methods of treating chest obstruction with traditional Chinese medicine. By studying the theory of yin deficiency and blood stasis in chest obstruction, we hope to further reveal its etiology and pathogenesis, clarify the core ideas and methods of treating chest obstruction with traditional Chinese medicine, and provide scientific guidance and basis for clinical practice.